Efecto de la utilización con las asociaciones de gramíneas – leguminosas en (UDIVI) pasto y forraje, hato bovino de la ESPAM “MFL” - Calderón Loor, Miguel Ángel (2016)
According to the study conducted in the forage species that are in the grasslands of the ESPAM-MFL different factors were analyzed in associations to grasses with leguminous in the unit of teaching, research and social outreach of herd bovine in the ESPAM-MFL, three treatments were used T1 paddocks with 63 % percent of grasses and 37 % percent of leguminous, T2 paddock with 71% percent of grasses and the 29 % percent of leguminous and T3 paddock with 78 % percent of grasses and the 22 % percent of leguminous. The variables evaluated were composition botanist(%), quality structural (g), composition chemistry of the floors (%) with the availability of green matter and dry matter (g /graze /m2) height species forages (cm) and the production of milk (kg milk/cow/day) the bests results corresponds to T1: green Matter 1697,67 g, dry matter 472 g, Star 48,33 cm, Saboya 118,67 cm, Shenna leguminous 70,67 cm, Desmodium leguminous 35,67 cm, 6,67 kg milk / cow / day, while that T3; green matter 978,67g, dry matter 322 g, Estrella 34,33 cm, saboya 44,33 cm, leguminous shenna 35,00 cm, leguminous desmudion 34,00 cm ,( 4,92 kg / milk/ cow/day) .It is suitable to apply the proportions that indicates T1 shows the best answers referring to production forage and dairy.